Angiotensinogen M235T polymorphism and susceptibility to hypertrophic cardiomyopathy in Asian population: A meta analysis. (December 2020) - Zhen, Zhen; Gao, Lu; Wang, Qin; Chen, Xi; Na, Jia; Xu, Xiwei; Yuan, Yue
Objective: To explore the relationship between the polymorphism of angiotensinogen gene (AGT) M235T and susceptibility to hypertrophic cardiomyopathy (HCM) in Asian population by meta-analysis. Methods: PubMed, Embase, Web of Science, Cochrane library, CNKI, Wan Fang, and other databases were searched to collect the literature about AGT M235T polymorphism and HCM from the inception to March 1, 2020. The Newcastle-Ottawa Scale (NOS) checklist was uesd to perform independent literature review and study quality assessment. Data was analyzed by Stata 15.0 software. Results: The results showed that, except for the recessive genetic model (TT vs MT+MM: OR = 1.27, 95%CI: 1.05–1.53), in the other four genetic models, the M235T polymorphism had no significant correlation with the risk of HCM (T vs M: OR = 1.17, 95%CI: 0.88–1.57; TT+MT vs MM: OR = 1.13, 95%CI: 0.55–2.33; TT vs MM: OR = 1.25, 95%CI: 0.60–2.59; TM vs MM: OR = 0.95, 95%CI0.5–1.82). The results of subgroup analysis showed that, except for the heterozygous genetic model, in the other four genetic models, M235T polymorphism was significantly associated with sporadic hypertrophic cardiomyopathy (SHCM), but not with familial hypertrophic cardiomyopathy (FHCM) ( p  > 0.05). Conclusion: M235T polymorphism in Asians is associated with HCM, especially SHCM. Heterozygotes increase the risk of patients with SHCM.